Study Protocol for 'PsilOCD: A Pharmacological Challenge Study Evaluating the Effects of the 5-HT2A Agonist Psilocybin on the Neurocognitive and Clinical Correlates of Compulsivity'. - O'Connor,S; Godfrey,K; Reed,S; Peill,J; Rohani-Shukla,C; Healy,M; Robbins,T; Frota,Lisboa Pereira de Souza A; Tyacke,R; Papasyrou,M; Stenbæk,D; Castro-Rodrigues,P; et al. (Cureus, 2025)
BACKGROUND: Obsessive-compulsive disorder (OCD) is a complex condition marked by persistent distressing thoughts and repetitive behaviours. Despite its prevalence, the mechanisms behind OCD remain elusive, and current treatments are limited. This protocol outlines an investigative study for individuals with OCD, exploring the potential of psilocybin to improve key components of cognition implicated in the disorder. The PsilOCD study strives to assess the effects of low-moderate psilocybin treatment (10 mg) alongside non-interventional therapy on several facets of OCD. The main focus points of PsilOCD are cognitive flexibility, measured with cognitive tests, and neuroplasticity, assessed through electroencephalography (EEG). METHODS: 20 blinded participants with OCD will complete two dosing sessions, separated by four weeks, where they will receive 1 mg of psilocybin on the first and 10 mg on the second. The first dose serves as an active placebo, and the latter is a low-moderate dose that induces relatively mild-moderate emotional and perceptual effects. Participants will be supported by trained psychedelic therapists, who will sit with them during each dosing session and provide virtual preparation and integration sessions over the 12-week study period. Therapeutic support will be the same for both the 1 mg and 10 mg sessions. PsilOCD's primary outcomes include scores in the intradimensional-extradimensional (ID-ED) shift task, which is an established measure of cognitive flexibility, and neuroplasticity as quantified by a visual long-term potentiation (vLTP) task. This task is delivered as part of an EEG paradigm and measures acute quantified changes in neuroplasticity in the brain's visual system. The ID-ED task will be conducted twice, two days after each dosing session, and the EEG recordings will also be taken twice, immediately after each session. Secondary outcome assessments will include OCD and affective symptom severity, as well as an array of patien